The Function and Meaning of Mantras in the Ngabungbang Ritual of Rancakalong - Usman Supendi; Anggy Giri Prawiyogi; Arga Adha Anwari; Abdul Wahab Junaedi (Journal of General Education and Humanities, 2026)
This study analyzes the functions and meanings of mantras in the Ngabungbang ritual in Rancakalong, Sumedang, as a representation of symbolic Islamization in Sundanese culture. The research addresses the limited studies examining oral ritual texts as media for cultural negotiation and religious transformation. The study aims to identify the ritual functions of the mantras, interpret their symbolic meanings, and explain their role in representing the spread of Islam within local traditions. A qualitative descriptive method with an ethnographic approach was employed. Data were collected through observation, interviews with traditional leaders and ritual practitioners, and documentation of five mantra texts used in the ritual. The analysis applied Paul Ricoeur’s hermeneutic theory and William R. Bascom’s folklore function theory. The findings reveal that the mantras function as media for purification, protection, gratitude, and social regulation. Their meanings reflect harmony between humans, nature, and divine power while demonstrating the integration of Islamic expressions, such as the shahada and prayers to Allah, into older Sundanese cosmological beliefs. The study highlights how Islamic teachings are culturally adapted through oral ritual traditions without entirely eliminating local identity.